Cancer incidence in Mozambique in 2015–2016: data from the Maputo Central Hospital Cancer Registry. Issue 4 (July 2019) - Carrilho, Carla; Fontes, Filipa; Tulsidás, Satish; Lorenzoni, Cesaltina; Ferro, Josefo; Brandão, Mariana; Ferro, Ana; Lunet, Nuno
Abstract : There is scarce information on cancer incidence in Mozambique. We aimed to describe cancer incidence data from the Cancer Registry of the Maputo Central Hospital (MCH) in 2015–2016, for Maputo City dwellers, and to compare the incidence rates with those observed in 1956–1961. Cancers with incidence data in 2015–2016 were identified by the Cancer Registry of the MCH. Crude and age-standardized incident rates (ASIR, per 100 000) – direct method, world standard population – were computed for Maputo City, under the assumption that most cancer cases among this population were identified at the MCH. A total of 1707 incident cases in Maputo City dwellers were registered (76.6% confirmed histologically). Prostate cancer, Kaposi sarcoma, and liver cancer were the most frequent in men (ASIR: 24.5, 19.8, and 13.3, respectively). Cervical and breast cancers, and Kaposi sarcoma were the most common among women (ASIR: 32.4, 11.8, and 9.5, respectively). Compared with the data from 1956 to 1961, the most pronounced declines in ASIR were for bladder and liver cancers, in both sexes, and increases were greater for prostate cancer among men (172.2%) and breast cancer (237.1%) among women. Our study highlights the high frequency of infection-related cancers in Maputo, but also of those related to the ongoing demographic and socioeconomic transition.